ASESMEN PERMASALAHAN PESERTA DIDIK DAN IMPLIKASINYA PADA PROGRAM BIMBINGAN DAN KONSELING DI SMA - Fitri, Indrya; Herdi, Herdi (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2025)
The Guidance and Counseling Program is the most important part in the implementation of Guidance and Counseling services in schools. In its preparation, it certainly cannot only be based on observation or limited to administrative needs by using assessments that do not measure the real needs and problems of students. This is an important discussion to understand that the use of appropriate assessments will provide accurate information, especially to find out the problems of students. For this reason, a problem assessment is needed to reveal data on the highest learner problems in what fields. This study uses a type of descriptive research with a quantitative approach in the form of a score or percentage of the results of the problem assessment. The research subjects were XII grade students at senior high school with the highest assessment results in the career field of 14.87%, learning 12.89%, personal 11.7%, and social 8.67%. The results of this study indicate that it is necessary to develop a service program in the career field to help students overcome career-related problems so that they can achieve maturity in developmental tasks regarding career insight career readiness.